Exploring servicescape experiences across museum types - Erdogan, Hasan Huseyin; Enginkaya, Ebru (EMERALD GROUP PUBLISHING LTD, 2023)
PurposePrevious research has been unable to provide a comprehensive method for measuring environment-based experience and its outcomes although it is an essential determinant of the museum experience. Therefore, this paper aims to present a measurement method for exploring how visitors' servicescape experiences affect their positive word-of-mouth intention (PWOM). Design/methodology/approachData were collected by surveying 810 visitors to 3 museums (i.e. Louvre, Pera and Key) representing different museum types. The research model was validated by using partial least squares structural equation modeling. FindingsThe predicted associations between sensory, spatial and social experiences, and PWOM were confirmed for Pera. In the Louvre and Key, however, only sensory and social experiences were positively associated with PWOM. In addition, the moderating effect of building type on the relationship between spatial experience and PWOM was demonstrated. Originality/valueThis paper contributes to the servicescape, customer experience and museum literature in several ways. Firstly, this study proposes a measurement method for servicescape experiences. Secondly, this study introduces servicescape experiences as new types of customer experience. Thirdly, this study provides insightful implications for the museum literature and professionals by highlighting how servicescape experiences affect PWOM across different types of museums.
Keywords: Customer experience; Servicescape; Word-of-mouth; Structural equation modeling; Museum; VISITOR EXPERIENCE; ATMOSPHERICS; ENVIRONMENT; BEHAVIOR; IMPACT; INTENTIONS; QUALITY; DESIGN; STORE; Business & Economics